(untitled) (Research, Society and Development, 2022)
Obesity is a chronic, multifactorial disease, responsible for several morbidities, and bariatric surgery is an efficient alternative for rapid weight loss. About 20 to 25% of patients, even losing weight after the procedure, tend to regain weight after the second year. This study aimed to analyze the evolution of segmental body composition in bariatric patients with weight regain and undergoing pharmacological therapy with liraglutide. This is a retrospective, longitudinal study through data analysis in the medical records of an institution specialized in clinical and surgical treatment of obesity. The sample was comprised of 22 bariatric patients treated between January 2016 and December 2019. Anthropometric data from segmental impedance measurements were collected, as well as data on the clinical evolution regarding the proposed treatment. The results showed that in both doses, the loss of mass was relevant in all segments, indicating significance. BMI reduced 9.3% in all patients in the 24 weeks analyzed. With 2.4mg/day of liraglutide, there was a 7.2% weight loss and, with a 3.0mg/day dose, the loss was 9.84% of the weight. Considering both doses, the overall weight loss was 9.2%.The percentages of mean differences in fat were similar between trunk and limbs. With respect to lean mass, although there was no statistical significance, we have a clinical significance of protection.